(3GdLOd aj GdCUhds - (3Ydj Hf Ybjd Hf eMeO Hf Ybjd GdHZOGOj GdXaQj, CHh GdhaGA, jYQa HGHf Ybjd,J (B513 (3g` s ((3eMehO Hf Ydi Hf GdUaG s)
(3ChdgG (B:s
(3hEfeG HOCJ HPcQ GdNdGa dCf GdLOd jfHfi Ydjg hdGjchf GdLOd eY GdGJaGb s
(3BNQgG (B:s
(3ajbhd YdbJ YdjgG MJi GdERGdI s
(3fSNI KGfjI ecQQI ef Qbe (B141 (3CUhd abgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B151s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs